Description of Patient Description of Patient Anxiety When Receiving Treatment in HospitalAnxiety When Receiving Treatment in Hospital: Description of Patient Anxiety When Receiving Treatment in Hospital - Afandi, Alfid Tri; Putri, Prestasianita; Rifai, Ahmad; Susanti, Ika Adelia (Universitas Bondowoso, 2024)
Background: Anxiety is a common response experienced by patients when receiving treatment in the hospital, often triggered by unfamiliar environments, interactions with medical personnel, and uncertainty about the results of treatment. This study aims to explore the level of anxiety in patients and the factors that influence it. Methods: This study used a descriptive survey method with a quantitative approach, involving 100 patients who received treatment at Hospital X. Data was collected via the Hamilton Anxiety Rating Scale (HARS) and analyzed using descriptive statistics and Pearson correlation analysis. Results: The results showed that 60% of patients experienced moderate anxiety, 25% experienced high anxiety, and 15% experienced mild anxiety. The analysis shows a significant positive relationship between length of stay and anxiety level (r = 0.42, p < 0.05) as well as a negative relationship between education level and anxiety (r = -0.35, p < 0.05). Conclusion: The discussion in this study highlights that environmental factors in hospitals and the quality of communication between medical personnel and patients significantly influence patient anxiety levels. These results are consistent with previous research showing the importance of a supportive environment and effective communication in reducing anxiety. Therefore, interventions aimed at improving the hospital environment and communication with patients are highly recommended to reduce anxiety and improve the quality of care.